Algebra

posted by .

please help me solve 3x-x+7=9+2x.

  • Algebra -

    combine like terms!

    (3x-x-2x)=9-7

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra Problem

    I've gotten confunsed. Please help. Solve: 2y-a = a + 3b ____ ______, for y 3 4 Please show how to solve this. If you mean (2y -a)/3 = (a + 3b)/4 then 2y - a = (3/4) (a + 3 b) 2y = (7/4) a + (9/4) b y = (7/8) a + (9/8) b f(x)=x(squared)-4x+9 …
  2. Math - Algebra

    Simplify and solve for x=2 and y=5. Please remember to group like terms. 1. 3x - 2y + 4x -3y 2. y + x - y - x 1. 3x2 - 2x5 + 4x2 - 3x5 6 - 10 + 8 - 15 2. 5+2-5-2 7-5+2 yah i think that's how to solve it, basically sub in the x and …
  3. Algebra

    FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x = -6 or 0 it would = 0 help me solve this problem.. solve for W: 2L+2W=38 please and thank you!
  4. Algebra II- please help!

    I just cannot seem to be able to grasp the concept of solving polynomial inequalities. Can someone please explain, step by step, how to solve them?
  5. Algebra

    Solve 3x +1 < 5 or 3x +1 > 4 By saying "solve," is it asking for me to show it on a line and in interval notation?
  6. Algebra (please help!)

    Pretend the parentheses are absolute value bars. Solve: (x+5) < 5 The choices are: a. -10 < x < 0 b. -5 < x < 5 c. -10 < x < 5 d. -10 < x < 10 I'm not sure how to solve this and how the answers relate to …
  7. college algebra

    please solve by method of substitution 0.3x-0.4y-0.33=0 0.1x + 0.2y -.21=0 please give all steps to solve.I think I understand the basic concept but this is little more complicated for me. Thanks in advance
  8. Algebra 2

    How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of 4) x > -24 & how do I solve these: 8^x+1=3 e^x+2=50 8logx=16 I really don't understand how to solve these so can someone please explain them to me?
  9. Algebra

    PLease ,Please ,Please help me solve this problems #1 Since x = 3y-4, -3(3y-4)+4y = -3 now just solve for y and then x #2 Since x = 4+4y, -(4+4y) = 4y=-4 or something Again, solve for y, then x
  10. Algebra

    Simplify this expression (DO NOT solve for x) 5x+6(x+2)-8(x-3) I have no clue, can someone tell me how to solve it?

More Similar Questions